2019
DOI: 10.3390/languages4040092
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Skills in Academic Writing: A Study on Coherence and Cohesion in Pakistani Research Abstracts

Abstract: Writing requires a suitable and strategic use of language with communicative potential and structural correctness. The use of coherence and cohesion helps create communicative potential and structural correctness in texts. This study aims to investigate the use of cohesive items in the abstracts of Pakistani research articles and thereby determine what type of cohesive items are frequently used by writers. In addition, the study aims to know what functions the said writers achieve through the most frequently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Under these assumptions, grammatical competence may be expected to show relationships with coherence as it may help to organise the text. The present as well as past studies such as Ahmad et al (2019), Garing (2014) and Saeed (2020) found that the organisation of the text bears a high correlation with coherence. Schleppegrell's (2004) work may help to explain why grammatical knowledge correlates with coherence at a lower level than morphological awareness.…”
Section: Discussionsupporting
confidence: 77%
“…Under these assumptions, grammatical competence may be expected to show relationships with coherence as it may help to organise the text. The present as well as past studies such as Ahmad et al (2019), Garing (2014) and Saeed (2020) found that the organisation of the text bears a high correlation with coherence. Schleppegrell's (2004) work may help to explain why grammatical knowledge correlates with coherence at a lower level than morphological awareness.…”
Section: Discussionsupporting
confidence: 77%
“…This sequence of incidents helps the reader to connect the ideas and infer the intended meaning of the writer. Well-organized and connected ideas are deemed to be the quality of essay writing and are given a higher score than ill-organized essays (Ahmad et al, 2019). Different theme-rheme progressions, as mentioned in the literature review section above, assist the writer to widen, broaden, and reiterate the topic which makes the organization of the essay free from any divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistani ESL/EFL learners and writing According to the benchmarks set by the Pakistani Education Policy 2006, graduate students should be expected to produce coherent and error-free pieces of written text as they are taught all these skills in their previous education. However, the situation is not very encouraging as most of the students are unable to write grammar-free and well-organized essays (Ahmad et al, 2019). Saeed (2020) also found that most of the essays written by adult ESL learners lacked organization and had frequent coherence breaks.…”
Section: 3mentioning
confidence: 99%
“…When one's own voice takes on the persona of an authority figure, the expected personal viewpoints in secondary school are traded for the ability to include authoritative others in a multi-perspective.Students must provide critical analyses of other academics' works when absorbing their ideas, both independently and in relation to other relevant materials.As beginners, many students are unaware that they are expected to assert authority in their papers; hence, they regard their assignment as a collection of objective and impersonal opinions from others. It is not without good reason that the term "academic writing" is not used to describe the writing that students perform in secondary schools but rather is limited to defining the writing performed at universities and beyond [7][8][9].…”
Section: Introductionmentioning
confidence: 99%